Socio-Demographic Determinants of the Experience of Physical Violence among Intimate Partners in Nigeria - Kolawole, Alonge Sunday; Precious, Adekanye Tolulope (Archives of Business Research, 2017)
In many cultures women are viewed and treated as inferior or as second-class citizens. Gender-based violence in all its forms is an on-going problem, even in the so-called developed world. Such violence has been associated with serious health consequences, including physical, sexual, and reproductive health, psychological and behavioural problems, as well as fatal health outcomes such as homicide, suicide, and maternal mortality. This paper examined the socio-demographic factors that may predispose a Nigerian woman to experience Intimate Partner Violence (IPV). The paper made use of secondary data from (raw data) NDHS 2013. Data were collected from 21,004 respondents comprising women of childbearing age who are currently married or in union with a partner. The variables required for the analysis were taken from the raw data and analysed using both the descriptive and inferential statistics. Women in the study population reported to have experienced at least one form of physical violence by their partner, slap is the most prevalent form of IPV observed from the findings of this study, also “offence” that was perceived to be the most justified for wife beating is if a woman goes out without telling. Findings also revealed the education level affects experience of IPV, also women with primary education are likely to experience IPV more. It was recommended that there should be a reduction in spousal age difference. Also the issue of child marriage should be abolished, for her to attain some maturity and get certain level of education that will equip her for the future.